Burning for enhanced non‐timber forest product yield may jeopardize the resource base through interactive effects. Issue 5 (27th July 2016) - Darabant, András; Dorji,; Staudhammer, Christina L.; Rai, Prem B.; Gratzer, Georg
Summary: Non‐timber forest product (NTFP) harvest is frequently accompanied by resource management practices that interact with the harvesting itself, other disturbances and abiotic conditions. These interactions, in turn, lead to diverse environmental effects. Few studies focus on these practices in the context of harvesting NTFPs, product properties and environmental impacts, including biological invasions. In Pine woodlands in Eastern Bhutan, Cymbopogon flexuosus East Indian Lemon Grass is harvested and distilled to obtain essential oil, an economically important NTFP. Prescribed fires are applied in late winter (before annual harvest in summer) to induce regeneration of new tillers with increased essential oil content. This practice is based on local ecological knowledge and renders the utilization of C. flexuosus economically viable. On two sites with contrasting stand structure, we evaluated the effects of different prescribed burning regimes (no burning vs. burning with two levels of frequency and intensity) on the sustainability of annually harvested C. flexuosus, regarding cover, biomass yield, essential oil yield and quality. At the same time, we evaluated the effects of prescribed burning on the spread of the invasive shrub Chromolaena odorata . Cymbopogon flexuosus biomass declined over time, likely as a result of harvesting. In more closed stands, it was moreover marginally negatively influenced by fire. We confirmed local ecological knowledge regarding significantly higher essential oil yield on burned plots, without differences between fire regimes. In open stands, fire led to rapid expansion of C. odorata, specifically with frequently applied, higher intensity fires. Additionally, the spread of C. odorata showed adverse effects on C. flexuosus cover. Synthesis and applications . Our results highlight the importance of studying the wider impacts of non‐timber forest product (NTFP) harvest. We confirmed local ecological knowledge that fire increases lemon grass essential oil yield, making prescribed burning an attractive land management tool for farmers. Nevertheless, the practice of annual harvesting may lead to resource decline that may be exacerbated by fire in closed stands. Caution needs to be practiced on open sites where invasive C. odorata may spread rapidly after fires. Management needs to focus on preventing concentration of annual harvesting and associated prescribed burning in the same areas. Amending national forestry rules to legalize fire as a land management tool can support local economies and potentially prevent wildfires that regularly devastate human infrastructure across eastern Bhutan. Abstract : Our results highlight the importance of studying the wider impacts of non‐timber forest product (NTFP) harvest. We confirmed local ecological knowledge that fire increases lemon grass essential oil yield, making prescribed burning an attractive land management tool for farmers. Nevertheless, the practice of annual harvesting may lead to resource decline that may be exacerbated by fire in closed stands. Caution needs to be practiced on open sites where invasive C. odorata may spread rapidly after fires. Management needs to focus on preventing concentration of annual harvesting and associated prescribed burning in the same areas. Amending national forestry rules to legalize fire as a land management tool can support local economies and potentially prevent wildfires that regularly devastate human infrastructure across eastern Bhutan.